“Plan de comercialización para potencializar el Agroturismo en la Granja Agroturística Santa Lucia, ubicada en el barrio Virgenpamba de la ciudad de Loja” - Paccha Chamba, Holger Eduardo (2024)
As an additional source of income to agricultural and livestock production, the Santa Lucía Agrotourism Farm offers agrotourism services. This family venture is located to the north of the city of Loja. Among its main activities are agricultural and livestock tasks aimed at self-consumption and sales. The farm is also in the process of implementing tourist attractions, in addition to conducting agrotourism activities where visitors can take a tour interacting with the farm animals, observe and harvest agricultural products, and enjoy a restaurant service offering typical dishes. To enhance the agrotourism activities carried out by the company, the present research has developed a marketing plan. This plan involves an internal analysis (company characterization) and an external analysis (market study based on 239 surveys). Market penetration and diversification marketing strategies were established. Four tactics and 16 activities (four for each tactic) were developed based on these strategies to position the company in the market. Among the main activities carried out in the research, we have the creation of the business philosophy, corporate image development, content creation for publication on social media platforms (Facebook, Instagram, TikTok), internal signage, among others. These activities, combined with constant innovation, will enable the company to establish a market position, achieving greater visibility and customer loyalty. Keywords: agrotourism, marketing, strategy, tactics, social